Assessing the Quality of Shellfish Harvesting Areas: The Case of the Oualidia and Sidi Moussa Lagoons in Morocco - Khbaya, K.; Bouthir, F-Z.; Cherkaoui, R.; Kabiri, E. M.; Chfiri, R.; Bessa, A. (European Scientific Journal, ESJ, 2024)
Based on European regulation 91/492/EC, Morocco, very early on, established legislation with conditions for producing and marketing live bivalve mollusks. In applying this legislation, the National Institute of Fisheries Research (INRH)[1] has set up a system for sanitary monitoring of the marine environment, through which several harvesting areas have been classified while others are in progress. In January 2020, the Oualidia and Sidi Moussa lagoons were categorized respectively in classes B and C, with 52.77% of the results falling between 230 and 4600 MPN E. coli/100 g of flesh and intravalvular liquid (FIL) and 11.11% of the results falling between 4600 and 46000 MPN E. coli/100 g FIL. Sidi Moussa Lagoon has been classified as a category C since 2006. Consequently, oyster farming activity has been suspended in this area. This incident serves as a warning sign of the significant weakness of these ecosystems in addressing multiple social and economic challenges. On the other hand, INRH has sufficient data and tools to progress toward better optimization of the marine environment and sanitary monitoring program management. [1] Institut National de Recherche Halieutique.